Mutually exclusive extracellular signal‐regulated kinase pathway mutations are present in different stages of multi‐focal pulmonary Langerhans cell histiocytosis supporting clonal nature of the disease. Issue 3 (29th April 2016) - Kamionek, Michal; Ahmadi Moghaddam, Parnian; Sakhdari, Ali; Kovach, Alexandra E; Welch, Matthew; Meng, Xiuling; Dresser, Karen; Tomaszewicz, Keith; Cosar, Ediz F; Mark, Eugene J; Fraire, Armando E; Hutchinson, Lloyd
Abstract : Aims: Pulmonary Langerhans cell histiocytosis (PLCH) is an idiopathic cigarette smoking‐related disorder of the lung. Molecular changes in cellular or fibrotic stages of PLCH have not been investigated. We studied the prevalence of extracellular signal‐regulated kinase (ERK) pathway mutations in different PLCH stages and other non‐PLCH smoking‐related lung diseases. Methods and results: The cohort included 28 PLCH with cellular ( n = 10), mixed cellular/fibrotic ( n = 4) and fibrotic histology ( n = 14). Seven cases had concurrent multi‐focal/multi‐lobar tumours. Respiratory bronchiolitis interstitial lung disease (RB‐ILD, n = 2), desquamative interstitial pneumonia (DIP, n = 4) and mixed RB‐ILD/DIP ( n = 2) were included for comparison. BRAF V 600E immunohistochemistry, next‐generation sequencing (NGS) and peptide nucleic acid (PNA) clamp polymerase chain reaction (PCR) with high analytical sensitivity (<0.1–0.2%) were used to analyse RAS, BRAF and MAP2K1 genes. Of 26 cases with gene mutation data, BRAF V 600E was identified in eight of 12 (67%) cellular cases and in one of 14 (7%) fibrotic cases. MAP2K1 or KRAS mutations were observed in four of 14 (29%) fibrotic cases and three of the 12 (25%) cellular cases. Multi‐focal/multi‐lobar specimens carried identical BRAF ( n = 5) or non‐hotspot MAP2K1 ( n = 2) mutations. The other smoking‐related disorders were negative for mutations. Patients with cellular lesions or BRAF mutation were significantly younger than patients with fibrotic or BRAF wild‐type PLCH. Conclusion: The presence of identical but mutually exclusive ERK pathway mutations in multi‐focal PLCH supports a neoplastic/clonal origin for this disease. Patient age and mutation type differed between cellular and fibrotic histology and may indicate a natural progression or a mutation‐specific pathogenicity.